Psychoanalysis and politics histories of psychoanalysis under conditions of restricted political freedom - Damousi, Joy.; Plotkin, Mariano Ben, 1961- (Oxford : Oxford University Press, 2012)
This volume explores a central paradox in the evolution of psychoanalytic thought and practice and the ways in which they were used. Why and how have some authoritarian regimes utilized psychoanalytic concepts of the self to envisage a new social and political order?
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Political psychology; Political ethics